Responding in a Pandemic: Student Nurse Educator Mentorships, the Other Side of Blackboard - Tolouian, Audrey; Monsivais, Diane B.; Wholeben, Melissa (European Scientific Journal, ESJ, 2021)
Background: Nurse educators who are novice often express the need for improved preparation in the educator role. Problem: With the growth of online programs, one area of concern is the need for educators who are prepared to teach online. Approach: A mentorship for online teaching was developed to give student nurse educators the opportunity to develop educator competencies in the online environment. The process, benefits, challenges, and key points for the success of the mentorship are discussed. Outcomes: Since Spring 2016, 89 nurse educator graduate students have completed the mentorship. Their confidence related to the educator role in an online environment was enhanced, and they took great pride in serving as professional role models to the undergraduate nursing students. Conclusions: The mentorship option provides improved educator role preparation for nursing education graduate students who will teach online. It also provides informal mentorship as well as an unexpected perceived value in higher education to students in undergraduate nursing program.